2018
DOI: 10.1080/13552600.2018.1440089
|View full text |Cite
|
Sign up to set email alerts
|

Moral disengagement and self-reported harassment proclivity in men: the mediating effects of moral judgment and emotions

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 73 publications
1
15
0
3
Order By: Relevance
“…Supporting our 3 rd hypothesis, the MDiISA scale was a predictor of IBSA proclivity, consistent with Bandura's (1986Bandura's ( , 1999 social cognitive theory and previous MD research (Pornari and Wood 2010, Robson and Witenberg 2013, Page and Pina 2018. This indicates that people who expressed greater levels of MD expressed a greater tolerance to perpetrating IBSA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Supporting our 3 rd hypothesis, the MDiISA scale was a predictor of IBSA proclivity, consistent with Bandura's (1986Bandura's ( , 1999 social cognitive theory and previous MD research (Pornari and Wood 2010, Robson and Witenberg 2013, Page and Pina 2018. This indicates that people who expressed greater levels of MD expressed a greater tolerance to perpetrating IBSA.…”
Section: Discussionsupporting
confidence: 86%
“…MD is positively correlated with sexual harassment proclivity (Page and Pina 2018) and cyber-aggression, although the association with cyber-aggression was weaker compared to traditional bullying (Pornari andWood 2010, Robson andWitenberg 2013). This suggests MD mechanisms facilitate the perpetration of other gendered and online harmful behaviour, hence they could also be implicated in or utilised for the perpetration of TFSV and IBSA.…”
Section: Introductionmentioning
confidence: 97%
“…Penelitian terdahulu menunjukkan anak yang berkonflik dengan hukum memang memiliki tingkat moral disengagement yang tinggi (Cardwell, Piquero, Jennings, Schubert, & Mulvey, 2015;Caroli & Sagone, 2014;DeLisi dkk., 2014;Dhingra, Debowska, Sharratt, Hyland, & Kola-palmer, 2015). Terkait dengan fenomena pencabulan, moral disengagement berkorelasi positif dengan kecenderungan pria melakukan pelecehan seksual di kantor (Page & Pina, 2015, 2018. Hasil penelitian ini sejalan dengan temuan bahwa tingkat moral disengagement pelaku kejahatan seksual ternyata lebih tinggi dibandingkan pelaku kejahatan non seksual (D'Urso, Petruccelli, Grilli, & Pace, 2019;Petruccelli dkk., 2017).…”
Section: Pendahuluanunclassified
“…Distorsi konsekuensi terjadi karena pelaku tidak bisa menempatkan dirinya pada posisi orang lain (Lane & Ryan, 2010) sehingga pelaku gagal mengenali dampak negatif yang dialami perempuan korban pencabulan (Bowes-Sperry & O'Leary-Kelly, 2014). Kadang-kadang pelaku pencabulan menganggap bahwa melakukan pencabulan pada perempuan nakal tidak akan menyebabkan dampak psikologis (Page & Pina, 2018). Persepsi ini didapat individu akibat tayangan pornografi yang menggambarkan perempuan sebagai objek seksual (Löfgren-Mårtenson & Månsson, 2010).…”
Section: Pembahasanunclassified
“…Kohlberg and Herch (1977) proposed a model of moral development in which RMA is related to lower levels of moral development (Kohlberg & Hersh, 1977;Wilson et al, 2002). On the other hand, Bandura (1968) indicated that mechanisms of moral disengagement are embodied in rape myths which are likely to result in blaming the rape victims and exonerate the rapist (Bandura, 1986;Page & Pina, 2018). One of the most comprehensive theories that attempt to address the roots of people's moral judgments is Moral Foundations Theory (Graham et al, 2013;Haidt, 2012).…”
Section: Introductionmentioning
confidence: 99%